PERAN MIKROBA AEROB DALAM PENGOLAHAN LIMBAH CAIR TEKSTIL - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2007)
The objective of this study is to understand the performance of microbial degradation activities in textile wastewater treatment unit. Result of BOD, COD, DO and microbial measurement indicated that DO concentration in activated sludge wastewater treatment unit was < 0.5 mg/L, ratio of BOD and COD was >1.99 and microbial density was around 1 x 107 ind/mL. Based on parameter measured, firstly, the DO concentration is not enough for biodegradation process but this condition still work for biofloculation process; secondly, the BOD and COD ratio is indicating that wastewater compound could not fully degrade, eventhough the microbial density in the wastewater unit is in normal number.